Structural changes in optical coherence tomography underlying spots of increased autofluorescence in the perilesional zone of geographic atrophy - Oishi, M; Oishi, A; Lindner, M; Pfau, M; Schmitz-Valckenberg, S; Holz, FG; Fleckenstein, M (Association for Research in Vision and Ophthalmology, 2017)
To investigate structural correlates corresponding to the appearance of increased fundus autofluorescence (FAF) in the perilesional area of geographic atrophy (GA) secondary to age-related macular degeneration.Serial FAF images of 181 eyes with GA of 134 patients participating in the Directional Spread in Geographic Atrophy study (NCT02051998) were screened for increased FAF spots that had developed during the review period. Thickness and reflectivity of the retinal pigment epithelium (RPE)-basal lamina complex, as well as the integrity of the external limiting membrane (ELM) and the ellipsoid zone (EZ), respectively, in corresponding optical coherence tomography (OCT) scans were compared between the time points before and after the appearance of increased FAF. Adjacent areas without development of abnormal FAF were assessed as internal control.A total of 36 areas (15 eyes) with de novo developed increased FAF spots and 54 control areas were included. Analysis of the corresponding OCT images revealed an increase in RPE-basal lamina complex thickness (31.8 ± 7.3 to 42.1 ± 11.9 μm [P < 0.001]) and reflectivity (reflectivity ratio: 1.42 ± 0.11 to 1.54 ± 0.27 [P = 0.009]) corresponding to an increased FAF signal while there was no significant change in control areas. Development of increased FAF spots was associated with disruption of the ELM and the EZ.Increase of RPE-basal lamina complex thickness and reflectivity was spatially and temporally associated with the development of increased FAF spots in eyes with GA. In addition, outer retinal disruption may contribute to the corresponding increased FAF signal.